N-Heterocycles hybrids: Synthesis, antifungal and antibiofilm evaluation. Issue 6 (19th March 2022) - Chauhan, Sunil; Verma, Vikas; Kumar, Devinder; Gupta, Ragini; Gupta, Siddhi; Bajaj, Avinash; Kumar, Ashwani; Parshad, Mahavir
Abstract: 2, 4, 5-Triaryl-1 H -imidazole hybrids were synthesized from substituted benzil and indole-3-aldehyde which on subsequent treatment with aryl azides converted to 1, 2, 3-triazoles by employing click chemistry. All the synthesized hybrids were characterized by FTIR, 1 H-NMR, 13 C-NMR spectroscopy and HRMS. These scaffolds were tested in vitro for their antifungal evaluation against different candida species. Screening against the used fungal strains, the results outcome that imidazole-indole hybrids bearing antifungals more effectively reduced than imidazole-indole-1, 2, 3-triazole hybrids with their MIC80 values in the range of 2–128 µg/mL. Among all the synthesized hybrids, 2a and 2b were found to be the most potent against fungal strains as a result of different methods like, time kill assays, effect on fungal membrane and antibiofilm activity. The docking simulations of the most active hybrids, 2a, 2b and 2c were carried out in the active site of sterol 14-alpha demethylase enzyme of Candida albicans . Graphical Abstract: UF0001